Comparison of potential inhibitors and targeting fat mass and obesity‐associated protein causing diabesity through docking and molecular dynamics strategies. Issue 11 (20th July 2021) - Kumar, S Udhaya; Rajan, Bithia; Kumar, D Thirumal; Cathryn, R Hephzibah; Das, Samprita; Zayed, Hatem; Emmanuel Jebaraj Walter, Charles; Ramanathan, Gnanasambandan; Priya Doss. C, George
Abstract: Genome‐wide association studies (GWAS) have identified an association between polymorphisms in the FTO gene and obesity. The FTO : rs9939609, an intronic variant, is considered a risk allele for developing diabesity in homozygous and heterozygous forms. This study aimed to investigate the molecular structure of the available inhibitors specific to the FTO mutations along with the rs9939609 variant. We identified the best‐suited inhibitor molecules for each mutant type containing the rs9939609 risk allele. Missense mutations unique to obesity and containing the risk allele of rs9939609 were retrieved from dbSNP for this study. Further stability testing for the mutations were carried out using DynaMut and iStable tools. Three mutations (G187A, M223V, and I492V) were highly destabilizing the FTO structure. These three mutants and native FTO were docked with each of the nine‐inhibitor molecules collected from literature studies with the help of PyRx and AutoDock. Further structural behavior of the mutants and native FTO were identified with molecular dynamics simulations and MM‐PBSA analyses, along with the 19complex inhibitor compound. We found the compound 19complex exhibited better binding interactions and is the top candidate inhibitor for the M223V and I492V mutants. This study provided insights into the structural changes caused due to mutations in FTO, and the binding mechanism of the inhibitor molecules. It could aid in developing antiobesity drugs for treating patients with mutations and risk alleles predisposing to obesity. Abstract : The FTO: rs9939609, an intronic variant, is considered a risk allele, in both homozygous and heterozygous forms, for developing diabesity. This study identified the best‐suited inhibitor molecule for each mutant type containing the rs9939609 risk allele. Our study identified 19complex is the best‐suited inhibitor for the native M223V and I492V FTO mutants.